Sales Application on Distro Souplay - Ade Bani Riyan (Politeknik Siber Cerdika Internasional, 2020)
The development of the business world is now inseparable from the support of technology, especially computer technology and information because in increasingly modern economic activities are needed the existence of computer technology to support and facilitate all economic activities in order to achieve these goals. With the use of computers as a tool in Distro Souplay does not mean without problems, there are still troublesome things and obstacles to create a comfortable and efficient atmosphere while in Distro suoplay. The accumulation of irregular goods data. The slow search for data needed when ordering an item of goods Adds knowledge and insights, especially about the sale of goods and implements the science obtained in lectures into the business world.